The Development of Social Science Module Based on the Integration of “Sedekah Bumi” as the Local Wisdom - Melisa, Melisa; Suprijono, Agus; Kasdi, Aminuddin (International Journal for Educational and Vocational Studies, 2020)
The reseacher is motivated by the the absence of a social science learning module (IPS) that integrates with “Sedekah bumi” as the local wisdom in conducting this research junior high school Menganti. Therefore a research on the development of IPS modules integrate the local wisdom on the diversity of Indonesian etnichs and cultures was conducting in classs 7th B of junior high school Menganti. This study aims to describe the feasibility of the IPS module in terms of validity and practicality. This research conducted using the development model with the R&D design of Borg and Gall (1975). The data in this study were obtained through a validation sheet and response questionnaire module. The results of the study show that: (1) module validity is based on the validation sheet in terms of valid category content and module validity in terms of display category is very valid, and (2) module practicality is based on a very practical category response questionnaire. From these results it can be concluded that the IPS module integrates the local wisdom of earth alms tradition is feasible to be used in the learning process.